Pengaruh Zakat Terhadap Tingkat Perekonomian Mustahik Pada Masa Pandemi Covid-19 Oleh BAZNAS Provinsi Banten Ditinjau Dari Perspektif Ekonomi Syariah - Hani Muflihah; Meri Lustianah (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2022)
Zakat is not just a reward-oriented worship, but also a social and humanitarian sense. The existence of zakat can help the economy of the community, especially mustahik. Activity restrictions due to the Covid-19 pandemic have affected economic activity nationally which then has an impact on the economy. BAZNAS Banten Province, is an official body formed by the government which has the task and function of collecting and distributing zakat, infaq, and alms (ZIS) to the community. BAZNAS Banten Province during the covid-19 pandemic had steps and programs on the utilization of zakat to help mustahik in dealing with the covid-19 pandemic. Whether or not the program is effective is an interesting thing to study. The purpose of this study is (1) to find out the steps and programs carried out by BAZNAS Banten Province to help the mustahik economy during the covid-19 pandemic (2) to determine the effect of zakat on the mustahik economy level during the covid-19 pandemic (3) to find out how is the sharia economic review on the effect of zakat on the mustahik economic level during the covid-19 pandemic by BAZNAS Banten Province. This study uses a combination of qualitative and quantitative research (mix methods). The sample of this study includes the total population of 33 people. Analysis of the research data using simple linear regression analysis and hypothesis testing using t test. The results of this study are that there are various programs and steps taken by BAZNAS Banten Province during the COVID-19 pandemic. The program includes mustahik training programs, business assistance programs, and workshop activities. Then from the results of the simple regression analysis test and hypothesis testing, there is a positive influence of zakat on the economic level of mustahik during the covid-19 pandemic by BAZNAS Banten Province. Likewise with the review of Islamic economic law, the effect of zakat on the mustahik's economic level is in accordance with the law, because its implementation is in accordance with the law of distributing zakat. This is also reinforced by the issuance of MUI fatwa no. 23 of 2020 concerning the Utilization of Zakat, Infaq, and Sadaqah Assets for Overcoming the Covid-19 Outbreak is allowed.